Mapping a new museum politics and practice of Latin American research with the British Museum - Sunnucks, Laura Osorio; Cooper, Jago; Miranda, Maria (Abingdon, Oxon Routledge, Taylor & Francis Group, 2022)
"Mapping a New Museum seeks to rethink the museum's role in today's politically conscious world. Presenting a selection of innovative projects that have taken place in Latin America over the last year, the book begins to map out possibilities for the future of the global museum. The projects featured within the pages of this book were all supported by The Santo Domingo Centre of Excellence for Latin American Research (SDCELAR) at the British Museum (BM), with the aim of making the BM's Latin American collections meaningful to communities in the region and others worldwide. These projects illustrate how communities manage cultural heritage and, taken together, they suggest that there is also no all-encompassing counter-narrative that can be used to "decolonise" museums. Reflecting on, and experimenting with, the ways that research happens within museum collections, the interdisciplinary collaborations described within these pages have used collections to tell stories that destabilise societal assumptions, whilst also proactively seeking out that which has historically been overlooked. The result is, the book argues, a research environment that challenges intellectual orthodoxy and values critical and alternative forms of knowledge. Mapping a New Museum contains English and Spanish versions of every chapter, which enables the book to put critical stress on the self-referentiality of Anglophone literature in the field of museum anthropology. The book will be essential reading for students, scholars and museum practitioners working around the world"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Santo Domingo Centre of Excellence for Latin American Research; Collectors and collecting -- Latin America; Latin America -- Antiquities -- Social aspects; Material culture -- Social aspects -- Latin America; British Museum -- Ethnological collections